Silencing S-Adenosyl-L-Methionine Decarboxylase (SAMDC) in Nicotiana tabacum Points at a Polyamine-Dependent Trade-Off between Growth and Tolerance Responses - Mellidou, Ifigeneia; Moschou, Panagiotis N.; Ioannidis, Nikolaos E.; Pankou, Chryssa; Gėmes, Katalin; Valassakis, Chryssanthi; Andronis, Efthimios A.; Beris, Despoina; Haralampidis, Kosmas; Roussis, Andreas; Karamanoli, Aikaterini; Matsi, Theodora; et al. (Frontiers in Plant Science, 2016)
Polyamines (PAs) are nitrogenous molecules that are indispensable for cell viability and with an agreed-on role in the modulation of stress responses. Tobacco plants with downregulated SAMDC (AS-SAMDC) exhibit reduced PAs synthesis but normal levels of PA catabolism. We used AS-SAMDC to increase our understanding on the role of PAs in stress responses. Surprisingly, at control conditions AS-SAMDC showed increased biomass and altered developmental characteristics, such as increased height and leaf number. On the contrary, during salt stress AS-SAMDC showed reduced vigor when compared to the WT. During salt stress, the AS-SAMDC plants although showing compensatory readjustments of the antioxidant machinery and of photosynthetic apparatus, they failed to sustain their vigor. AS-SAMDC sensitivity was accompanied by inability to effectively control H2O2 levels and concentrations of monovalent and divalent cations. In accordance with these findings, we suggest that PAs may regulate the trade-off between growth and tolerance responses.